Financial institutions and the allocation of talent - Vesa Kanniainen; Mikko Leppämäki (Bank of Finland, 2002)
The paper shows that uninformed finance gives rise to excessive entry, both in human-capital-intensive and in conventional industries when the financial institutions cannot identify the entrepreneurial talent.Introduction of informed capital (eg venture capital finance) with superior screening ability results in an institutional equilibrium with efficiency gains in human-capital industries.Contrary to received wisdom, the institutional equilibrium with informed capital is characterised by more limited entry to an industry, which requires highly talented human capital. Unexpectedly, the total welfare effect is ambiguous, as the allocation of non-informed capital is now less efficient in the conventional industry.The institutional equilibrium is shaped by investors' risk preferences, costs of establishing uninformed and informed capital, and the initial distribution ot talent in the economy.
URN:NBN:fi:bof-20140807304
Keywords: D82; G24; 330; allocation of talent; asymmetric information; financial institutions; venture capital; institutional equilibrium